Rural primary school principals’ leadership strategies for ICT integration - Nhlumayo, Buhle Stella (Research in Social Sciences and Technology- OpenED Network, 2024)
This paper explored the factors influencing the leadership strategies of school principals in rural primary schools regarding the integration of information and communication technologies (ICTs) in the process of teaching and learning in their schools. School principals are responsible for ensuring that there is ICTs integration in their schools’ teaching and learning processes. Embedded within the theory of learning-centred leadership (LCL), school principals have a responsibility to lead, foster, manage, and support the learning process for teachers and learners in their schools. Thus, school principals need to be well acquainted with innovative technologies for teaching and learning amidst the Fourth Industrial Revolution (4IR), which is global, complex, and fast-paced, to lead learning through ICT integration. Underpinned by the interpretive qualitative approach and using a multiple case study as a research design, this study generated data from three selected South African rural primary schools through face-to-face interviews with the three school principals. Data were analysed thematically. Findings revealed that school principals’ leadership strategies are influenced by their attitudes towards ICT integration into teaching and learning, their exposure to ICT workshops, and their own judgements of their abilities in using ICT. The paper recommends customised in-service training for school principals and teachers to alter and improve their exposure to, attitudes, perceptions toward ICT integration in teaching and learning.